Optimizing Maceration Extraction of Myristicin and Methyl Eugenol from Nutmeg (Myristica fragrans Houtt.): An RSM Box–Behnken Approach - Utami Dyah Syafitri; Deden Saprudin; Budi Riza Putra; Dewi Murniati; Irmanida Batubara (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Myristicin is the key marker of nutmeg (Myristica fragrans) quality, while methyl eugenol is an undesirable compound requiring strict monitoring. This study aimed to optimize the extraction conditions of these compounds from nutmeg seeds and mace as a pretreatment step prior to electrochemical quantification. Optimization was performed using Response Surface Methodology (RSM) with a Box–Behnken Design (BBD), considering extraction time (h), ethanol concentration (%), and the sample-to-solvent ratio (g/mL) as independent variables. The analytes were quantified by Gas Chromatography–Mass Spectrometry (GC-MS), and the experimental data were modeled using Design Expert software. Regression models indicated that ethanol concentration and solvent volume significantly influenced extraction yields, while extraction time had a statistically minimal effect (p-values > 0.05, small effect sizes). Nevertheless, practical differences were observed between matrices: nutmeg seeds reached optimal extraction within 2 hours, whereas mace required 17 hours, likely due to its higher essential oil content and fibrous structure, which slows diffusion kinetics. Thus, although time effects were not statistically significant, extended extraction was practically preferred for mace to ensure adequate recovery. Response definitions were specified as follows: Y1 = myristicin concentration (mg/mL), Y2 = methyl eugenol concentration (mg/mL), and % extraction yield. The optimal extraction conditions were achieved with 90% ethanol and 50 mL solvent, maximizing analyte detectability while maintaining reproducibility across seed and mace extracts. These optimized ethanolic matrices are compatible with subsequent electrochemical quantification, given their aqueous/ethanolic composition and anticipated sensitivity of electrochemical detection.